Remarks on generalized solutions of some ordinary nonlinear differential equations of second order in the Colombeau algebra - Ligęza, Jan (Annales Mathematicae Silesianae, 1996)
In this article some equations of second order are considered, whose nonlinearity satisfies a global Lipschitz condition. It is shown that the equations with additional conditions admit unique global solutions in the Colombeau algebra ????(ℝ1).